First record of Falsanathelges Boyko & Williams, 2003 (Crustacea: Isopoda: Epicaridea: Bopyridae) from Japan, with the description of a new species - Shinoda, Haruki; Fujita, Hiroki; Nakano, Tomoyuki; Shimomura, Michitaka (Zootaxa, 2025)
Falsanathelges grandiceps sp. nov. is described as an abdominal bopyrid of hermit crab Cancellus mayoae in the Nansei Islands, southwestern Japan. Falsanathelges grandiceps sp. nov. is distinguished from its congeners by the following combination of characters: head longer than broad, head approximately one-fourth of body in length head anterior margin convex, ischium and basis of all pereopods without large lobe in female, pleopods and lateral plates broadly ovate, base of uropods without peduncle, and biramous uropods in female and pleon subovate, all pleomeres fused with no lateral indication of segmentation, and pleon posterior margin with a pair of tubercles in male. This is the third species described in the genus, and the first species of the genus being found in Japan. The others in the genus are from Malaysia, Indonesia, Philippines and Taiwan. An amended generic diagnosis and key to species are provided.